Health-related quality of life in primary and secondary adrenal insufficiency. (December 2014) - Aulinas, Anna; Webb, Susan M
<x xml:space="preserve">Abstract</x> Adrenal insufficiency (AI) is characterized by a deficient production of glucocorticoids with or without associated mineralcorticoid and/or adrenal androgen deficiencies. Despite the low prevalence of AI, its impact on the affected patient is very high, and can be life-threatening disease if not adequately treated. Several glucocorticoid treatment regimens are available, but none is capable of perfectly imitating the cortisol circadian rhythm. Cortisol rhythmicity and treatment of other possible concomitant conditions often associated (e.g., autoimmune disorders and panhypopituitarism) are essential to improve outcome of AI. Morbidity often present in treated AI include an unhealthy metabolic profile, bad quality of sleep, infertility, sexual dysfunction and worse health-related quality of life. This review focuses on psychological morbidity and impaired quality of life in patients with primary or secondary AI of any origin, including a special section devoted to congenital adrenal hyperplasia.